2011
DOI: 10.1097/ccm.0b013e3182227b97
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan reduces heart failure after cardiac surgery: A prospective, randomized, placebo-controlled trial*

Abstract: In the present study, levosimendan infusion reduced the incidence of heart failure in cardiac surgery patients but was associated with arterial hypotension and increased requirement of vasopressor agents postoperatively. Improved mortality or morbidity was not demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 33 publications
3
46
0
3
Order By: Relevance
“…Of these, 16 studies were further excluded because there were no outcome data, and further details could not be obtained by the authors. Five eligible randomized clinical trials were identified and included in the final analysis [37][38][39][40][41] (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…Of these, 16 studies were further excluded because there were no outcome data, and further details could not be obtained by the authors. Five eligible randomized clinical trials were identified and included in the final analysis [37][38][39][40][41] (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…We recruited newborns (age less than 30 days) undergoing risk-adjusted classification for congenital heart surgery (RACHS) [19] 3 and 4 procedures who received a 72 h continuous infusion of 0.1 lg/kg/min levosimendan and we compared them with newborns, who did not receive levosimendan. The dose was chosen on the basis of studies in adult patients [8][9][10][11][12][13] and personal experience on selected cases. We excluded newborns with major congenital associated malformations (not classified by RACHS score), sepsis, renal or liver failure before surgery, or the need for inotropic drugs before surgery.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Levosimendan (Simdax; Orion Pharma, Espoo, Finland), a novel inodilator agent belonging to the family of calcium sensitizer agents [8], has shown preconditioning effects and positive inotropic and vasodilating properties that successfully contributed to treat congestive heart failure and postcardiotomic heart dysfunction in adults [9][10][11]. So far, few data exist on levosimendan use in pediatric patients, mostly related to the treatment of heart failure [12]; nevertheless, its unique pharmacodynamics suggest a strong rationale for levosimendan use in immature hearts requiring surgery on cardiopulmonary bypass (CPB) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Katsaragakis et al (100) showed that preoperative levosimendan treatment may be safe and efficient for the perioperative optimization of heart failure in patients undergoing noncardiac surgery. In a clinical trial reported by Lahtinen et al (101) with 200 patients, levosimendan infusion reduced the incidence of heart failure in cardiac surgery patients but was associated with arterial hypotension and increased requirement of vasopressor agents postoperatively and no effect was demonstrated on mortality or morbidity. Finally, in a recent metaanalysis reported by Harrison et al (102) including 14 randomised clinical trials, Levosimendan was associated with reduced mortality and other adverse outcomes in patients undergoing cardiac surgery, and these benefits were greatest in patients with reduced ejection fraction (EF).…”
Section: +mentioning
confidence: 99%